(untitled) (Scientific journal of the Fergana State University, 2026)
The article reveals the role of the Great Silk Road in the history of world civilization and its influence on the development of science, culture, and spirituality. The study analyzes the process of knowledge and idea exchange between the East and the West through the Silk Road. It also highlights the international significance of the scientific heritage of such scholars as Al-Khwarizmi, Al-Biruni, Ulughbek, and Ibn Sina.